KEPASTIAN HUKUM PENYEDIA JASA DIGITAL PADA PLATFORM TELEKOMUNIKASI DI INDONESIA - Nabila Syahrapi , Disca; Helviana Nai, Helena; Ancylia Zukandi, Nabhila; Ainun Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Legal certainty for digital service providers operatingon telecommunication platforms in Indonesia. The rapid growth of digital telecommunication platforms has facilitated the emergence of various digital service providers that rely on online platforms to conduct business transactions. In Indonesia, Telegram has become one of the most widely used platforms due to its ease of communication, user anonymity, and features that support digital business activities. However, this development has also been accompanied by a significant increase in digital fraud, causing substantial losses to consumers and highlighting the lack of legal certainty governing digital service providers operating through such platforms. This study aims to examine the legal certainty surrounding digital service providers on telecommunication platforms in Indonesia, identify the challenges in law enforcement, and formulate regulatory improvements to strengthen legal protection for both business operators and consumers. The research employs a normative juridical method using statutory, conceptual, case, and comparative approaches. Data were collected through library research, including legislation, academic literature, court decisions, and other relevant documents concerning electronic system administration and digital fraud offenses. The findings indicate that the existing legal framework governing digital service providers on telecommunication platforms still contains significant regulatory gaps, particularly regarding identity verification, platform accountability, and consumer protection mechanisms. Therefore, stronger regulations on business account verification, enhanced inter-agency coordination, and greater cross-border cooperation are necessary to establish greater legal certainty and foster a safer digital ecosystem.